Case Report: Weakness and Recurrent Falls in an Older Patient - Mercedes Galloway; Nannette Hoffman; Christopher Lawrence Bray; Ahmed Ebrahim; Brittany Puebla; David Ritchie (Geriatrics)
Background/Objectives: Lower-extremity weakness in older adults is often overlooked, yet it can have reversible or medical causes that contribute to increased falls. Common factors include vision disturbances, impaired balance due to otolith dysfunction, arthritis-related immobility, and lower-extremity neuropathy. This case presents a unique diagnostic challenge in evaluating bilateral lower-extremity weakness and recurrent falls in an older adult, highlighting the complexity of diagnosing conditions with overlapping symptoms. Case Presentation: The patient, a woman with a history of a neuroendocrine tumor, experienced progressive weakness in her lower extremities, along with oculomotor and facial muscle involvement, despite extensive testing. Key clinical findings included elevated protein levels in cerebrospinal fluid, suggesting the possibility of an infectious or autoimmune process. A thorough investigation was conducted, including testing for both common and rare conditions such as Guillain–Barré syndrome, Lyme disease, and tuberculosis. Results: Despite comprehensive diagnostic efforts, no clear etiology was identified. The patient’s condition was eventually considered to be related to carcinomatosis meningoencephalitis, a rare complication from a previous cancer diagnosis. Given the progressive nature of her symptoms and lack of treatment options, she was transitioned to palliative care. Conclusions: This case highlights the importance of a comprehensive differential diagnosis in older patients with unexplained weakness and falls. Rare neurological conditions should not be overlooked, even when more common causes are suspected. Clinicians should remain aware that falls and weakness in older adults may stem from various pathologies, some of which are reversible if identified early, and rare causes must always be considered when standard treatments fail.